The Dilemmas Sorted: A Story of Being Supervised - Sabri Sabri (Universitas Islam Negeri (UIN) Mataram, 2010)
Writing is an important expression of human experiences. In this article, I try to (re)present my experience as a supervisee. I employ autobiographical or autoethnographical style to portray an incident within which my supervisor and I were involved in a meaningful interactive supervision processes. Some references quoted are not to frame the idea of my writing, but rather, as a referent which could justify, confirm, or criticize my experience. The use of the first single person style is legitimized and the question of whether this kind of writing is scientific or not, should be put aside when we were within the context of qualitative inquiry.